MASLAHAH MURSALAH SEBAGAI METODE DALAM PENETAPAN HUKUM ISLAM - Haika, Ratu (Mazahib, 2013)
At ushul fiqh study, has been negotiated that there were four sources of Islamic Law, namely Al Qur’an, Hadits, Ijma’ and Qiyas.  At its development also many methods that known as determination of Islamic Law, including maslahah mursalah.  Maslahah divided into three area, namely accepted by syara’, ignored by syara’ and be debated by fuqaha because there were no postulate both accept and also ignore that.  the third ones that become the object of maslahah mursalah theory or a term introduced by Imam Malik.  Maslahah mursalah as a method or source of legal determination is used by some of ulama but some others especially from follower of mazhab asy-Syafi’iyah denied whereas based on the research results, Imam asy-Syafi’I and follower, Imam Gazhali, accept it.